PHASE RELATIONS OF A SERPENTINE COMPOSITION BETWEEN 5 AND 14 GPA: SIGNIFICANCE OF CLINOHUMITE AND PHASE E AS WATER CARRIERS INTO THE TRANSITION ZONE - Stalder R.; Ulmer P. (My University, 2001)
Run products from high pressure experiments at 800-1,200 C and 5-14 GPa (corresponding to depths of 150 to 420 km) on a serpentine bulk composition [close to Mg3Si2O5(OH)4] were analysed by optical microscopy, micro-Raman spectroscopy and electron microprobe. All charges exhibit strong chemical zoning. Fluid, melt and hydrous solids were mostly concentrated at the top, bottom and along the wall of the capsules. The central part of the charge was devoid of H2O. Both fluid and hydrous magnesian phases exhibit a Mg/Si ratio higher than forsterite. In contrast, the centre of the capsule was enriched in SiO2. The observed zoning can neither be explained by gravitational settling nor by a thermal gradient alone. Most likely the fluid was separated from the solids by surface forces and thereby established the chemical gradient by preferentially dissolving MgO. If strong chemical zoning is taken into account, the occurrence of more phases than allowed by the phase rule can be explained by separating the bulk into several domains of different bulk compositions. Results indicate that small amounts of F increase the stability field of clinohumite, Mg9Si4O16(OH,F)2, compared to OH-clinohumite in pure MSH previously reported. Clinohumite coexists with enstatite up to 975 C at 5 GPa, and up to 1,100 C at 12 GPa. At 14 GPa (close to the a/b-Mg2SiO4 transition) phase E becomes the most important water carrier. The new results indicate that clinohumite could be an important mantle mineral for transporting water into the Earth's transition zone due to its high thermal stability compared to other important water carriers such as serpentine and phase A.